The Extent of Seasonally Suitable Habitats May Limit Forage Fish Production in a Temperate Estuary - Fabrizio, Mary C.; Tuckey, Troy D.; Bever, Aaron J.; MacWilliams, Michael L. (Frontiers in Marine Science, 2021)
The sustained production of sufficient forage is critical to advancing ecosystem-based management, yet factors that affect local abundances and habitat conditions necessary to support aggregate forage production remain largely unexplored. We quantified suitable habitat in the Chesapeake Bay and its tidal tributaries for four key forage fishes: juvenile spotted hake Urophycis regia, juvenile spot Leiostomus xanthurus, juvenile weakfish Cynoscion regalis, and bay anchovy Anchoa mitchilli. We used information from monthly fisheries surveys from 2000 to 2016 coupled with hindcasts from a spatially interpolated model of dissolved oxygen and a 3-D hydrodynamic model of the Chesapeake Bay to identify influential covariates and construct habitat suitability models for each species. Suitable habitat conditions resulted from a complex interplay between water quality and geophysical properties of the environment and varied among species. Habitat suitability indices ranging between 0 (poor) and 1 (superior) were used to estimate seasonal and annual extents of suitable habitats. Seasonal variations in suitable habitat extents in Chesapeake Bay, which were more pronounced than annual variations during 2000–2016, reflected the phenology of estuarine use by these species. Areas near shorelines served as suitable habitats in spring for juvenile spot and in summer for juvenile weakfish, indicating the importance of these shallow areas for production. Tributaries were more suitable for bay anchovy in spring than during other seasons. The relative baywide abundances of juvenile spot and bay anchovy were significantly related to the extent of suitable habitats in summer and winter, respectively, indicating that Chesapeake Bay habitats may be limiting for these species. In contrast, the relative baywide abundances of juvenile weakfish and juvenile spotted hake varied independently of the spatial extent of suitable habitats. In an ecosystem-based approach, areas that persistently provide suitable conditions for forage species such as shoreline and tributary habitats may be targeted for protection or restoration, thereby promoting sufficient production of forage for predators. Further, quantitative habitat targets or spatial thresholds may be developed for habitat-limited species using estimates of the minimum habitat area required to produce a desired abundance or biomass; such targets or thresholds may serve as spatial reference points for management.